Wilfrid Sellars and phenomenology intersections, encounters, oppositions - De Santis, Daniele 1983-; Manca, Danilo 1987- (Ohio University Press, 2023)
"This collection offers the first systematic, comparative analysis of Wilfrid Sellars's Pittsburgh school of thought and Husserlian phenomenology. Beginning with an introduction to contemporary philosophical debates about the mind and pragmatism, the essays examine and clarify the discursive divide between analytic and Continental philosophy"--
Keywords: Sellars, Wilfrid -- 1912-1989; Phänomenologie; Phenomenology; Sellars, Wilfrid; Husserl, Edmund / 1859-1938; Aufsatzsammlung